Real‐Time Contact Force Sensing for Pulmonary Vein Isolation in the Setting of Paroxysmal Atrial Fibrillation: Procedural and 1‐Year Results. (6th November 2013) - MARIJON, ELOI; FAZAA, SAMIA; NARAYANAN, KUMAR; GUY‐MOYAT, BENOIT; BOUZEMAN, ABDESLAM; PROVIDENCIA, RUI; TREGUER, FREDERIC; COMBES, NICOLAS; BORTONE, AGUSTIN; BOVEDA, SERGE; COMBES, STEPHANE; ALBENQUE, JEAN‐PAUL
Real‐Time Contact Force Sensing for Pulmonary Vein Isolation Introduction The additional benefit of contact force (CF) technology during pulmonary vein isolation (PVI) for paroxysmal atrial fibrillation (AF) to improve mid‐term clinical outcome is unclear. Methods and Results Eligible patients with symptomatic paroxysmal AF were enrolled in this prospective trial, comparing circular antral catheter ablation (guided by Carto 3 System, Biosense Webster) using either a new open‐irrigated CF catheter (SmartTouch Thermocool, Biosense Webster) (CF group) or a non‐CF open‐irrigated catheter (EZ Steer Thermocool, Biosense Webster) (control group). Overall, 30 patients were enrolled in each group, with a standardized 12‐month follow‐up, free of antiarrhythmic therapy. Demographic, cardiovascular and anatomic characteristics were similar in both groups. Though complete PVI was eventually achieved in all cases in both groups, success using an exclusive anatomic approach was 80.0% in CF group versus 36.7% in control group (P < 0.0001). CF use was associated with significant reductions in fluoroscopy exposure (P < 0.01) and radiofrequency time (P = 0.01). The incidence rates of AF recurrence were 10.5% (95% CI, 1.38–22.4) in the CF group, and 35.9% (95% CI, 12.4–59.4) in the control group (log rank test, P = 0.04). After adjustment on potential confounders, the use of CF catheter was found to be associated with a lower AF recurrence (OR 0.18, 95% CI 0.04–0.94, P = 0.04). Conclusion Our findings suggest a potential benefit of real‐time CF sensing technology, in reducing AF recurrence during the first year after PVI.